Dendrimers as drug delivery vehicles: a comprehensive review: Pattern and application of dendrimers - Zorab, Musa M.; Qadir, Amjad Mahmood; Ahmed, Azad Mohammed Aziz (Cellular and Molecular Biology, 2025)
Dendrimers are chemical compounds that have functional groups on their surface and a hyperbranched structure. It is simple to promote the functionality of dendrimers and produce a variety of biocompatible products by altering their terminal groups. These materials have exceptional physicochemical characteristics that make them more beneficial in the administration of medications. They have a vigorous amount of potential as agents for nanomedicine applications because of their rare properties, which compose internal cavities, strong reactivity, globular form, solubility in water, and nanoscale size. They might also be synthesized easily. In-depth information about dendrimer composition and classifications, synthesis, and applications in nanomedicine, particularly drug delivery, is mentioned in this paper. Dendrimers are chiefly categorized by their functional groups, which permit for concise encapsulation of active compounds and structural imitatively of biomaterials. A rare property not often seen in other polymers serves to stabilize the surface of dendrimers to broaden their solubility in water. Dendritic molecules own a different variety of applications, such as dendrimers, dendrons, dendronized polymers, and hyperbranched polymers, which are organized based on their molecular weight. The role-play of dendrimers’ is the capability to attach a broad range of chemical entities and their ability to shift pharmacokinetic and pharmacodynamic features through tailored drug delivery. To sum up, this study bolded how dendrimers’ intricate structure and versatility make them excellent drug delivery vehicles since they may exactly modify their properties to reach special requirements. Drugs can be aimed at neuroinflammatory disorders and made more soluble and stable by dendrimers, which also deliver for a diversity of modes of delivery. Additionally, they show attractive ability in gene transfection and sensor production, drawing near their potential for a difference of usages in industries including pesticide delivery and medicine. With the potential to send out gene therapy, medicine delivery, and other specialties of science and medicine, dendrimers are becoming a huge crucial in the pharmaceutical and medical industries through the next research and clinical investigations.